17β-estradiol modulates the viability, phenotype, endocytosis, and inflammatory cytokine expression of RAW264.7 macrophages. (April 2016) - Yang, Linsong; Ting, Yue; Shen, Yuhuan; Wang, Liqun; Zhuang, Ziheng
17β-estradiol (E2) is a female sex steroid hormone and exerts a pivotal role not only in female pregnancy but also in organ immune responses. Macrophages, as a kind of antigen-presenting cells, play an important influence on the cellular and humoral immune responses and also express the E2 receptor. In the present study, we explored the effects of E2 on the viability, endocytosis, surface molecule, and inflammatory cytokine expression of RAW264.7 macrophages. Results showed that E2 slightly increased the cell proliferation and endocytosis of RAW264.7 cells, while notably decreasing the mRNA and protein levels of inflammatory cytokines such as tumor necrosis factor (TNF)-α and monocyte chemoattractant protein-1 (MCP-1). As for the expression of surface molecules closely associated with the functions of macrophages, E2 significantly reduced the levels of CD40, CD80, and MHC-II. Interestingly, E2 reduced the levels of CD86 at low dose (10 nM and 1 nM), while enhancing its expression at high doses (1 μM and 0.1 μM). These results suggest that E2 may play an immuno-suppressive role in the inflammatory reactions and some autoimmune diseases partly by influencing the expressions of some important surface molecules and inflammatory cytokines of macrophages.